2019
DOI: 10.3390/ijerph16224521
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Discrimination Is Associated with Housing Instability among Trans Women Living in the San Francisco Bay Area

Abstract: Trans women face numerous structural barriers to health due to discrimination. Housing instability is an important structural determinant of poor health outcomes among trans women. The purpose of this study was to determine if experiences of intersectional anti-trans and racial discrimination are associated with poor housing outcomes among trans women in the San Francisco Bay Area. A secondary analysis of baseline data from the Trans *National study (n = 629) at the San Francisco Department of Public Health (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…This was primarily experienced in childhood, and had flow-on effects throughout their lives. Such findings align with international literature which indicates that people who identify as LGBTIQ+ and have experienced homelessness have also experienced a great deal of instability (particularly housing instability) throughout their lives [ 76 78 ]. Krause et al [ 78 ] found that instability for LGBTIQ+ youth was rooted in early life experiences; this aligns with the findings presented in this paper showing numerous and wide-ranging instabilities experienced in childhood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was primarily experienced in childhood, and had flow-on effects throughout their lives. Such findings align with international literature which indicates that people who identify as LGBTIQ+ and have experienced homelessness have also experienced a great deal of instability (particularly housing instability) throughout their lives [ 76 78 ]. Krause et al [ 78 ] found that instability for LGBTIQ+ youth was rooted in early life experiences; this aligns with the findings presented in this paper showing numerous and wide-ranging instabilities experienced in childhood.…”
Section: Discussionsupporting
confidence: 87%
“…Krause et al [ 78 ] found that instability for LGBTIQ+ youth was rooted in early life experiences; this aligns with the findings presented in this paper showing numerous and wide-ranging instabilities experienced in childhood. Furthermore, the international literature shows that instability is worsened for those who hold multiple stigmatised identities, and that those who experience it face greater level of discrimination on the basis of LGBTIQ+ identity [ 76 , 77 ]. These findings, along with the corresponding international literature, show that there are a number of common experiences amongst LGBTIQ+ people prior to them experiencing homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim of the Trans National cohort study was to assess HIV incidence among trans women living in four cities around the world, and the methods are explained elsewhere. 23,24 Respondent-Driven Sampling was used to obtain a diverse sample of hard-to-reach adult trans women from the community in San Francisco in 2016. Eligibility criteria were (1) 18 years and older, (2) resident of San Francisco by self-reporting living in San Francisco, (3) assigned male sex at birth and identified as a gender other than man (e.g., female, trans woman, woman, nonbinary, gender queer), and (4) spoke English or Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…The diversity of the trans women community necessitates an intersectional approach to address the complexity of the lived experiences of trans women. The benefits of an intersectionality framework and approach for public health policies have been previously described [24,25]. In particular, a focus on the specific intersection of race and gender is crucial to understanding both antitrans and racial discrimination and designing programs and resources that are effective among trans women who are marginalized at the intersection of race and gender [24].…”
Section: Discussionmentioning
confidence: 99%